2019
DOI: 10.3390/ijms20020300
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Functions of Autophagy in Liver Physiology and Liver Diseases

Abstract: Autophagy is a catabolic process by which eukaryotic cells eliminate cytosolic materials through vacuole-mediated sequestration and subsequent delivery to lysosomes for degradation, thus maintaining cellular homeostasis and the integrity of organelles. Autophagy has emerged as playing a critical role in the regulation of liver physiology and the balancing of liver metabolism. Conversely, numerous recent studies have indicated that autophagy may disease-dependently participate in the pathogenesis of liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 607 publications
(776 reference statements)
0
60
0
2
Order By: Relevance
“…Autophagy is one of the pro-survival processes allowing hepatocytes to resist cellular stressors such as anoxia and nutrient starvation [112]. Autophagy protects hepatocytes from damage and cell death by clearing damaged organelles and misfolded proteins generated in hepatic disease [113].…”
Section: Autophagy Plays An Essential Role In Hepatic Physiological Pmentioning
confidence: 99%
“…Autophagy is one of the pro-survival processes allowing hepatocytes to resist cellular stressors such as anoxia and nutrient starvation [112]. Autophagy protects hepatocytes from damage and cell death by clearing damaged organelles and misfolded proteins generated in hepatic disease [113].…”
Section: Autophagy Plays An Essential Role In Hepatic Physiological Pmentioning
confidence: 99%
“…Autophagy acts as a bodyguard to protect cells, which involves concerted action to promote cell survival, for example in a state of stress when the cells are starved of nutrients or in case of a viral infection [5,10]. The importance of autophagy has been emphasized in case of CHC, since it promotes HCV persistence and suppresses the activated immune response [15].…”
Section: Discussionmentioning
confidence: 99%
“…Altered lipid metabolism is linked to the life cycle of HCV considering that virions coated with lipoproteins facilitate hepatocyte entry via lipoprotein receptors, however, the HCV-induced ER-stress leads to steatosis [ 3 ]. Intracellular lipid droplets being in excess in the cells are degraded by an autophagy process called lipophagy [ 3 – 5 , 22 ]. Vescovo et al reported that autophagy acts against the alterations in lipid metabolism induced by HCV and steatosis may develop when autophagy is disrupted [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the percentage of type1 NI with immunoposivity for p62 and cathepsin B was higher in NASH than in the controls without steatosis. The association of hepatocellular carcinogenesis with p62 is documented [38][39][40][41] . In mouse HCC models it was shown that p62 is required in progression from premalignancy www.nature.com/scientificreports/ to malignancy; high p62 expression protected HCC-initiating cells from oxidative stress-induced death 41 .…”
Section: Discussionmentioning
confidence: 99%